Three Years' Experience. Issue 5 (September 2019) - Harper, Mary G.; Maloney, Patsy
Abstract : Since its publication in 2016, the third edition of Nursing Professional Development: Scope and Standards of Practice has generated excitement for the specialty. The scope and standards has promoted uniformity of title, stimulated changes in position descriptions, fostered adherence to scope of practice, and served as a unifying framework for system-wide nursing professional development departments. However, continued action is required in the areas of advocacy, research, and engagement with the specialty organization.